STRENGTHENING COLLABORATION BETWEEN SCHOOLS AND REGIONAL CHILD PROTECTION COMMISSION IN PREVENTING BULLYING BEHAVIOR IN WEST PONTIANAK - Monica, Ega; Fitriani, Suci; Pratiscia, Imelda; Hastiani, Hastiani; Trisnowati, Eli; Sukmawati, Ema; Nurniyati, Niyah; Isriyah, Mudafiatun (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
Bullying is a negative behavior carried out by individuals or groups, both verbally and non-verbally, causing psychological impacts such as pressure, discomfort, and a loss of self-confidence. This community service activity was initiated by the Pontianak City Regional Child Protection Commission (KPAD) in response to the high prevalence of bullying and the low level of public awareness regarding children's rights. The purpose of this program is to strengthen public understanding of child protection and to support the formulation of more adaptive policies. The method used includes outreach in schools in West Pontianak, involving students and parents in interactive discussions. The program implementation covered the planning, presentation of materials, and reflection sessions. The result showed increased participant engagement and understanding, as indicated by their responses during discussions and follow-up actions such as forming child protection task forces. This program is expected to contribute to sustainable and effective child protection efforts in Pontianak.